A System for Management of Urbanized Areas in the Aspect of Acoustic Effects - KOMPAŁA, Janusz (Archives of Acoustics, 2011)
Within the boundaries of many municipal urbanized areas, large grounds are found, from which the noise is emitted into the environment, surrounded by the regions liable to acoustic protection. Such a condition generates many problems including also those ones related to the lack of the fulfillment of requirements concerning environmental protection against excessive noise. Therefore the aim of vital importance is the proper management of municipal grounds, both in view of the investment in policy steering, especially of new investments, and in the case of activities aimed at maintaining or restoring (revitalizing) the acoustic properties on the grounds that have already been used or simply degraded before. Keeping the scale of the problem in mind, such activities must be carried on not temporarily, but must have a systemic character. The structure of every system is characterized by the appropriate relationships among their elements and the properties of those relationships. In case of the noise management system, the elements of such a system are the activities connected with the management itself that are the actions which rely on specifying the aims and causing their realization within the scope and on the grounds subject to the managing entity. The superior aim of such activities should be to supply the tools for improvement of management and in the process of taking decisions that relate to investments including the of optimization conditions and maintenance of socio-economic importance of such areas.